Relation between flow-pressure-diameter studies in experimental stenosis of rabbit and human small bowel. Issue 8 (August 1990) - Morel, P; Alexander-Williams, J; Rohner, A
Abstract : Patients with inflammatory and ischaemic bowel diseases seem to tolerate narrowing of the gut lumen to a critical degree of stenosis without obstructive symptoms. To determine the physical factors involved in bowel occlusion, we created an experimental model using New Zealand rabbits in acute experiments under general anaesthesia. At operation a loop of small bowel was isolated and canulated, proximally for perfusion and pressure recording and distally to monitor flow. Having established the physiological pressure and flow conditions in a normal loop of gut, a stenosis was created using circular adjustable rings of determined widths. Pressure and flow were measured constantly and the variables studied were luminal diameter, stenosis length, and perfusate viscosity. This experimental model was reproduced using resected segments of human small bowel. We found a critical point- at 60% of the original diameter-down to which the small bowel is able to maintain normal flow. At a diameter smaller than this, the physiological parameters are rapidly altered up to the point of complete obstruction. In the rabbit model bowel rupture occurs at 30% of the initial size. Increased viscosity of the fluid and length of the stenosis alter this critical point inducing a larger critical diameter. We did not observe any cumulative effect of multiple identical stenoses.